(untitled) (Journal of Asian Development Studies, 2026)
The present study examined if any significant relationship exists among mutual trust of spouses, their marital relationship satisfaction and subjective feelings of happiness. The sample comprised of 45 couples selected from Shaheed Benazir Bhutto Women Univeristy, Peshawar and Hazara University, Abbottabad using convenience sampling technique. Age range of men was 24 to 68 years (M=39 ,SD=9.25) whereas ,the age range of women was 23 to 59 years (M=32 ,SD=6.30 ).Three Scales namely Trust Scale, Relationship Assessment Scale and Subjective Happiness Scale were used to measure the three constructs (mutual trust, marital relationship satisfaction and subjective feelings of happiness).It was hypothesized that scores on all these three scales will show high correlation with each other. It was further assumed that the subjective feelings of happiness will be higher among individuals who show higher levels of mutual trust. Our findings supported the hypotheses i-e Trust and Relationship Assessment Scale are strongly correlated, (r=0.63,p<.001).Similarly, Relationship Assessment Scale and Subjective Happiness Scale show high correlation with each other (r=0.68,p<.001).The findings also confirm that high scorers on Trust scale obtained significantly higher scores on Subjective Happiness as compared to the low scorers,(p<.003).